Gender and Precarious Research Careers A Comparative Analysis - Murgia, Annalisa; Poggio, Barbara (Taylor & Francis, 2018)
The literature on gender and science shows that scientific careers continue to be characterised - albeit with important differences among countries - by strong gender discriminations, especially in more prestigious positions. Much less investigated is the issue of which stage in the career such differences begin to show up. Gender and Precarious Research Careers aims to advance the debate on the process of precarisation in higher education and its gendered effects, and springs from a three-year research project across institutions in seven European countries: Italy, Belgium, the Netherlands, Iceland, Switzerland, Slovenia and Austria. Examining gender asymmetries in academic and research organisations, this insightful volume focuses particularly on early careers. It centres both on STEM disciplines (Science, Technology, Engineering and Mathematics) and SSH (Social Science and Humanities) fields. Offering recommendations to design innovative organisational policies and self-tailored 'Gender Equality Plans' to be implemented in universities and research centres, this volume will appeal to students and researchers interested in fields such as Gender Studies, Sociology of Work and Industry, Sociology of Knowledge, Business Studies and Higher Education.